Meta-analysis of the association between cysticercosis and epilepsy in Africa. - (:unkn) unknown (My University, 2010)
PURPOSE: The association between cysticercosis and epilepsy has been widely studied in Latin America and Asia and has proven to be one of the main causes of epilepsy. Despite high prevalences of both diseases in Africa, their association remains unclear. In this article we quantified the strength of the association between epilepsy and cysticercosis in Africa and we proposed some guidelines for future studies. METHODS: We performed a systematic review of literature on cysticercosis (considered as exposure) and epilepsy (considered as the disease) and collected data from both cross-sectional and case-control studies. A common odds ratio was estimated using a random-effects meta-analysis model of aggregate published data. RESULTS: Among 21 retrieved documents, 11 studies located in 8 African countries were included in the meta-analysis. Odds ratio of developing epilepsy when presenting cysticercosis (defined as Taenia solium seropositivity) ranged from 1.3-6.1. Overall, association between cysticercosis and epilepsy was found significant with a common odds ratio of 3.4 [95% confidence interval (CI) 2.7-4.3; p < 0.001]. DISCUSSION: The variability of the association found between the studies could be due to differences in study design or in pathogenesis of cysticercosis. Further studies should overcome identified problems by following some guidelines to improve epidemiologic and clinical assessment of the association. Better understanding of the relation between cysticercosis and epilepsy is a key issue in improving prevention of epilepsy in Africa.
Keywords: African Research